Implant Stability Changes for a Single Implant Mandibular Overdenture - Fouda, Karim; Fahmy, Ahmed; Aziz, Khaled; Aal, Marwa Abdel; Naguib, Amr; Nabi, Nouran Abdel (European Journal of Dentistry, 2021)
Objectives To compare the changes in implant stability for the nonsubmerged and submerged protocols for a single-implant retained mandibular overdenture using Cendres and Metaux Locator attachment throughout a 24-month follow-up.Materials and Methods Eighty edentulous patients who were seeking to install a single implant in the midline of the completely edentulous mandible. At the day of implant installation, patients were randomized into two groups using sealed envelopes: the nonsubmerged and submerged groups. After 3 months of healing period, randomization using sealed envelopes was performed and patients were randomized to receive the Cendres and Metaux Locator attachment. The periotest readings were recorded using the Periotest M device, every 3 months for the first year and annually in the second year. The scope of this clinical trial focused only on results of the Cendres and Metaux attachment.Statistical Analysis The Mann–Whitney U-test was used for comparison between study groups for independent samples. Two-sided p-values less than 0.05 were considered statistically significant.Results There was no statistically significant difference between the mean periotest readings of both groups throughout the 24-month follow-up. Both groups showed an improvement in mean periotest readings with the submerged group tending to show greater stability at 6, 12, and 24-month follow-ups.Conclusions The nonsubmerged and the submerged healing protocols resulted in reliable periotest readings with the submerged group showing greater improvement than the nonsubmerged, although this improvement is nonsignificant when using the Cendres and Metaux attachment for a single mandibular overdenture.
Keywords: nonsubmerged; Periotest; single-implant retained mandibular overdenture; submerged